Synthesis and evaluation of novel 18F‐labeled quinazoline derivatives with low lipophilicity for tumor PET imaging. (2nd February 2018) - Chong, Yan; Chang, Jin; Zhao, Wenwen; He, Yong; Li, Yuqiao; Zhang, Huabei; Qi, Chuanmin
Abstract: Four novel 18 F‐labeled quinazoline derivatives with low lipophilicity, [ 18 F]4‐(2‐fluoroethoxy)‐6, 7‐dimethoxyquinazoline ([ 18 F]I ), [ 18 F]4‐(3‐((4‐(2‐fluoroethoxy)‐7‐methoxyquinazolin‐6‐yl)oxy)propyl)morpholine ([ 18 F]II ), [ 18 F]4‐(2‐fluoroethoxy)‐7‐methoxy‐6‐(2‐methoxyethoxy)quinazoline ([ 18 F]III ), and [ 18 F]4‐(2‐fluoroethoxy)‐6, 7‐ bis (2‐methoxyethoxy)quinazoline ([ 18 F]IV ), were synthesized via a 2‐step radiosynthesis procedure with an overall radiochemical yield of 10% to 38% (without decay correction) and radiochemical purities of >98%. The lipophilicity and stability of labeled compounds were tested in vitro . The log P values of the 4 radiotracers ranged from 0.52 to 1.07. We then performed ELISA to measure their affinities to EGFR‐TK; ELISA assay results indicated that each inhibitor was specifically bounded to EGFR‐TK in a dose‐dependent manner. The EGFR‐TK autophosphorylation IC50 values of[ 18 F]I, [ 18 F]II, [ 18 F]III, and[ 18 F]IV were 7.732, 0.4698, 0.1174, and 0.1176 μM, respectively. All labeled compounds were evaluated via cellular uptake and blocking studies in HepG2 cell lines in vitro . Cellular uptake and blocking experiment results indicated that[ 18 F]I and[ 18 F]III had excellent cellular uptake at 120‐minute postinjection in HepG2 carcinoma cells (51.80 ± 3.42%ID/mg protein and 27.31 ± 1.94%ID/mg protein, respectively). Additionally, biodistribution experiments in S180 tumor‐bearing mice in vivo indicated that[ 18 F]I had a very fast clearance in blood and a relatively high uptake ratio of tumor to blood (4.76) and tumor to muscle (1.82) at 60‐minute postinjection.[ 18 F]III had a quick clearance in plasma, and its highest uptake ratio of tumor to muscle was 2.55 at 15‐minute postinjection. These experimental results and experiences were valuable for the further exploration of novel radiotracers of quinazoline derivatives. Abstract : Novel F‐18 labeled quinazoline derivatives with low lipophilicity for tumor PET imaging.